Sanksi Hukum Bagi Pasien Tidak Jujur Terinfeksi Corona Virus Disease 2019 - Gede Dana Semara Putra; I Nyoman Putu Budiartha; l Made Minggu Widyantara (Warmadewa Press, 2021)
The Indonesian government issued Presidential Decree No. 11 of 2020 concerning Public Health Emergencies as a serious warning of the threat of Covid-19. The delivery of dishonest information from a patient suspected of being infected with Covid-19 is an action to prevent the response to an outbreak that threatens the lives of people around him, including transmission to health workers who care for him. This study was formulated to figure out the legal sanctions for Covid 19 patients who were dishonest about their health conditions, and to find out the efforts made by the government in providing protection to health workers in handling Covid-19 patients. The research method used in the implementation of this research is normative legal research with an approach to the concept of legislation and the opinions of experts regarding to the law. The results showed that the application of strict sanctions to obstruction of the epidemic prevention measures could result in criminal penalties based on Law No. 4 of 1984 concerning Outbreaks of Infectious Diseases. As for the efforts made by the government to provide protection to health workers from the threat of Covid-19, it is given both preventively and repressively. Based on the results of this study, it can be concluded that patients who are not honest about their health conditions who have been infected with Covid-19 can be given a criminal penalty because this action is assumed as the way to prevent the government in overcoming the epidemic of infectious diseases that are currently hitting the community, then the government has also provided protection for health workers who treat patients infected with Covid-19 in a preventive and repressive manner.